Trajectory Tracking for Underwater Swimming Manipulators using a Super Twisting Algorithm. Issue 1 (10th August 2018) - Borlaug, Ida Louise G.; Gravdahl, Jan Tommy; Sverdrup‐Thygeson, Jørgen; Pettersen, Kristin Y.; Loria, Antonio
Abstract: The underwater swimming manipulator (USM) is a snake‐like, multi‐articulated, underwater robot that is equipped with thrusters. One of the main purposes of the USM is to act like an underwater floating base manipulator. As such, it is essential to achieve good station‐keeping and trajectory tracking performance for the USM by using the thrusters and by using the joints to attain the desired position and orientation of the head and tail of the USM. In this 'paper, we propose a sliding mode control (SMC) law, specifically the super‐twisting algorithm with adaptive gains, for the trajectory tracking of the USM's centre of mass. A higher‐order sliding mode observer is proposed for state estimation. Furthermore, we show the ultimate boundedness of the tracking errors. We demonstrate the applicability of the proposed control law and show that it leads to better performance than a linear PD‐controller.